Pengaruh Model Project-Based Learning (PjBL) Berbasis Notebooklm terhadap Sikap Kreatif dan Hasil Belajar Mahasiswa pada Mata Kuliah Desain Media Pembelajaran - Vita Indri Febriani; Astija Astija (JOEAI (Journal of Education and Instruction), 2026)
This study investigates the comparative effects of (1) conventional learning, (2) Project-Based Learning (PjBL), and (3) PjBL integrated with NotebookLM on undergraduate students' creative attitudes and learning outcomes in the Instructional Media Design course. A quasi-experimental design with a non-equivalent three-group pretest-posttest control group was employed. Participants were 103 students distributed across three intact classes: a control group (n = 34) receiving conventional instruction, Experiment 1 (n = 34) using PjBL, and Experiment 2 (n = 35) using PjBL integrated with NotebookLM as an AI-assisted research tool. Data were collected using a validated 32-item creative attitude scale (α = 0.89) and a 40-item cognitive achievement test (KR-20 = 0.87). Data were analysed using one-way ANOVA followed by Tukey HSD post-hoc tests and normalized gain (N-Gain) scores. Results showed significant differences across groups for both creative attitude (F = 47.82, p < .001, η² = .40) and learning outcomes (F = 54.37, p < .001, η² = .45). Post-hoc tests confirmed that Experiment 2 significantly outperformed both Experiment 1 and the control group on all measures (p < .001). N-Gain scores for Experiment 2 reached 0.60 (creative attitude) and 0.66 (learning outcomes), compared to 0.43 and 0.51 for Experiment 1, and 0.27 and 0.36 for the control group. These findings suggest that while PjBL alone improves learning, its integration with AI-powered tools such as NotebookLM yields substantially greater gains in creativity and achievement.   Keywords: Project-Based Learning; Notebooklm; Creative Attitude; Learning Outcomes